Pemberdayaan Kader Posyandu Lansia dengan Pengenalan dan Pelatihan Optimasi Active Aging - Berliany Sipollo; Achmad Syukkur (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Efforts to improve and maintain public health including the older adult are carried out based on non-discriminatory, participatory and sustainable principles. The government has formulated various health and social service policies for the older adult aimed at improving the quality of life of the older adult, achieving a happy and efficient old age in family and community life in accordance with their existence. Health and social services at the community level are posyandu for the older adult. The services provided at the posyandu are the spearhead of service in implementing government policies to achieve healthy, independent and efficient older adult people. Objective: Older adult care giver in Pandansari need to be empowered in recognizing the duties and obligations of older adult care giver and posyandu activities that cannot be separated from the concept of active aging, namely healthy, independent, and efficient older adult. Method: Community service has been carried out for 3 days, namely providing education about the efficient and effective posyandu for the older adult, cross-sectoral collaboration, various types of posyandu activities for the older adult, and direct simulation of the posyandu for the older adult. Result: The post-test results showed that 79% of care giver knew about efficient and effective posyandu activities for the older adult, 70% of care giver knew how to measure the older adult's blood pressure, 70% of care giver knew how to calculate BMI, and 72% of care giver knew about older adult gymnastics. Conclussion: older adult Posyandu cadres know their duties and obligations as older adult Posyandu cadres, it is proven that there is an increase in knowledge and skills of older adult Posyandu cadres in carrying out older adult Posyandu activities in supporting active aging (healthy, independent and efficient older adult) in Pandansari Village, Poncokusumo District.